The Role of Principal’s Instructional Leadership in Improving Teacher Performance: A Case Study at SMPN 3 Baleendah - Helmawati, Helmawati; Muchtar, Hendi Suhendraya; Suryana, Ana; Mulyati, Mulyati (Jurnal Visionary : Penelitian dan Pengembangan dibidang Administrasi Pendidikan, 2025)
Instructional leadership plays a crucial role in improving educational quality in schools, particularly by enhancing teacher performance. This study, conducted at SMPN 3 Baleendah, aims to analyse the implementation of the principal’s instructional leadership in supporting effective learning processes tailored to modern student needs. Using a qualitative approach and case study method, data were collected through in-depth interviews, direct observations, and documentation on the planning, implementation, and evaluation of instructional programs. Findings indicate that the principal applies strategies such as adaptive curriculum development, teacher competency programs through training and workshops, and regular evaluations of learning processes. Challenges, including limited facilities and technology adaptation, were addressed through collaboration with teachers and support from the school committee. The study underscores that the principalâ€™s participative and innovative approach positively impacts teacher performance and educational quality. Keywords: Instructional Leadership, Teacher Performance, Competency.